2019
DOI: 10.1038/s41598-019-51560-8
|View full text |Cite
|
Sign up to set email alerts
|

A collagen gel-coated, aligned nanofiber membrane for enhanced endothelial barrier function

Abstract: Herein, a collagen gel-coated and aligned nanofiber membrane named Col-ANM is developed, which remarkably improves endothelial barrier function by providing biochemical and topographical cues simultaneously. Col-ANM is fabricated by collagen gel coating process on an aligned polycaprolactone (PCL) nanofiber membrane, which is obtained by a simple electrospinning process adopting a parallel electrode collector. Human umbilical vein endothelial cells (HUVECs) cultured on Col-ANM exhibit remarkably enhanced endot… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
34
0

Year Published

2019
2019
2022
2022

Publication Types

Select...
9

Relationship

2
7

Authors

Journals

citations
Cited by 47 publications
(34 citation statements)
references
References 47 publications
0
34
0
Order By: Relevance
“…In the literature, different approaches can be found to reach this goal. Often a high-speed rotating collector is used [21][22][23], but fiber orientation can also be reached by using a pair of blades as the collector [24,25] or stretching the electrospun mat in ethanol [2].…”
Section: Introductionmentioning
confidence: 99%
“…In the literature, different approaches can be found to reach this goal. Often a high-speed rotating collector is used [21][22][23], but fiber orientation can also be reached by using a pair of blades as the collector [24,25] or stretching the electrospun mat in ethanol [2].…”
Section: Introductionmentioning
confidence: 99%
“…9 The biological properties of polymeric nanofibrous scaffolds can be improved by modifying their surface with biocompatible and bioactive materials. [10][11][12] Several works have used bioceramics to cover the surface of nanofibers to simultaneously benefit from their advantageous. These bioceramic-coated nanofibers have been shown to improve the process of osteogenesis in vitro and in vivo.…”
mentioning
confidence: 99%
“…Apparently, the substrate has therefore no discernible influence on the fiber diameter. On the other hand, partially conductive substrate areas can influence the orientation of electrospun nanofibers [13][14][15]. Figure 5 depicts the FFT analysis of the HIM images shown in Figure 2, as well as the HIM images color-coded according to the fiber orientations.…”
Section: Resultsmentioning
confidence: 99%
“…In previous studies, we have shown that DSSCs can be purely electrospun [11], and have investigated the influence of different foil materials on DSSC properties [12]. The main objective of this study is to investigate the adhesion of nanofibers directly electrospun onto different substrates and the influence of the conductive substrate on fiber diameter and orientation [13][14][15]. The combination of conductive foils, which contain carbon materials in particular and can thus be used as counter electrodes, with insulating nanofiber mats is highly interesting, since the latter can be used to hold liquid electrolytes [11].…”
Section: Introductionmentioning
confidence: 99%